USULAN PERBAIKAN DEFECT PADA SABLON PLASTIK MENGGUNAKAN METODE POKA YOKE DI CV. BAYOR PRINT 69 - Achmad Faizal; Novita Yanti Nababan; M. Edgar Jatnika (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
Abstract The main key for a company to survive and compete in the MEA era is to focus on quality, both product quality and quality in the production process. Quality improvement is a major concern for the company. Quality improvements make the defect product can be reduced to a minimum until it reaches zero defect. This study aims to determine the quality of Plastic Screen Printing products, analyze the types of product defects and defects in the production process, priority product defects, the root causes of disabilities, and the proposed improvement in CV. BAYOR PRINT 69. This study uses primary data obtained from direct interviews with relevant informants and uses secondary data in the form of production data and Plastic Screening defect data CV. BAYOR PRINT 69 in January-December 2018. The informants in this study consisted of employees who worked at CV. BAYOR PRINT 69. This study was analyzed using Pareto diagrams, fish bone diagrams, and brainstorming techniques. From the results of the analysis, it can be concluded that: (1) the quality of Plastic Screen Printing products is relatively good, (2) the most defects are found in the A1 defect group, namely the paint which is melted on the plastic, (3) humans are the factors causing the most defects, (4) the solution improvement that can be applied is to apply the three functions of the poka yoke method, namely warning, control, and shut down, as well as the addition of the machine operator. Keywords: Poka yoke, six sigma, zero defect